2020
DOI: 10.4103/sjg.sjg_447_19
|View full text |Cite
|
Sign up to set email alerts
|

Serum mucin 3A as a potential biomarker for extrahepatic cholangiocarcinoma

Abstract: Background/Aims: The aim of this study is to evaluate serum mucin 3A (MUC3A) as a candidate biomarker for extrahepatic cholangiocarcinoma (EHCC). Patients and Methods: 35 Patients with EHCC, 30 patients with pancreatic cancer, 35 patients with gallbladder carcinoma and 78 patients with benign biliary disease were enrolled during January 2015 to January 2016. Serum MUC3A, carbohydrate antigen 19-9 (CA19-9) and carcinoembryonic antigen (CEA) were measured in these patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…In addition, our previous study revealed that the serum CCDC25 level could distinguish in vivo 37: 294-303 (2023) CCA from benign biliary disease (BBD) (7). Furthermore, serum CCDC25 levels could discriminate CCA patients from HC more effectively compared with commonly used biomarkers including CEA and CA19-9 (15)(16)(17)(18)(19), and liver function tests including AST, ALT, and ALP. In addition, the results showed no correlation between serum ALP, CEA, CA19-9 levels and CCDC25 levels in CCA which are consistent with our previous study and indicated that CA19-9 and CEA were not correlated with serum CCDC25 levels in CCA patients (7).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, our previous study revealed that the serum CCDC25 level could distinguish in vivo 37: 294-303 (2023) CCA from benign biliary disease (BBD) (7). Furthermore, serum CCDC25 levels could discriminate CCA patients from HC more effectively compared with commonly used biomarkers including CEA and CA19-9 (15)(16)(17)(18)(19), and liver function tests including AST, ALT, and ALP. In addition, the results showed no correlation between serum ALP, CEA, CA19-9 levels and CCDC25 levels in CCA which are consistent with our previous study and indicated that CA19-9 and CEA were not correlated with serum CCDC25 levels in CCA patients (7).…”
Section: Discussionmentioning
confidence: 99%
“…The role of MUC3A in the occurrence and development of various tumors indicates its broad prospects in tumor treatment. Previous studies have found differences in the expression levels of MUC3A in cholangiocarcinoma and adjacent tissues, and the expression of MUC3A is closely related to patient survival, suggesting its value in the treatment of cholangiocarcinoma (20). Targeted drugs can be developed to delay patient survival.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found that human bile contains MUC1, MUC3A, and MUC5B, and there are differences in the expression levels of MUC3A in cholangiocarcinoma and adjacent tissues, with the expression status of MUC3A impacting the survival of patients with cholangiocarcinoma (20). However, the role of MUC3A in the development of cholangiocarcinoma and its mechanism remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, dysregulated MUCs are reported to serve as potential biomarkers in multiple tumor types. For instance, serum MUC3A is a potential diagnostic biomarker for extrahepatic cholangiocarcinoma [11]; high expression of MUC3A is associated with localized clear-cell renal cell carcinoma [12]; bone marrow MUC4 expression had significant prognostic value in acute myeloid leukaemia [13].…”
Section: Introductionmentioning
confidence: 99%